Leishmania sp. amastigotes identification in canine transmissible venereal tumor - Carreira, Vinicius Soares [UNESP]; Ferrari, Heitor Flavio [UNESP]; Langohr, Ingeborg Maria; Mackenzie, Charles; Montezzo, Luiz Carlos; Taira, Edson [UNESP]; Floeter-Winter, Lucile Maria; Luvizotto, Maria Cecília Rui [UNESP] (Hindawi, 2014)
Leishmaniasis is a vector-borne disease with Leishmania chagasi being the etiological agent of canine visceral leishmaniasis in South America. Canine venereal tumor is a transplantable round cell tumor of histiocytic origin which is mostly observed in sexually active male and female intact dogs. It has been shown that Leishmania amastigotes have higher tropism for the canine male genital tract tissues and venereal leishmaniasis transmission has been documented in dogs but, to date, a canine venereal tumor-dependent transmission route has not been fully demonstrated. In this report, a 10-year-old, mixed breed, intact female dog presented a vaginal venereal transmissible tumor but no other clinical abnormalities otherwise. Unexpectedly, tumor tissue imprint smears examination revealed Leishmania sp. amastigotes within infiltrating macrophages. In addition to the cytological direct identification, the protozoan was confirmed within the neoplastic tissue by means of immunohistochemistry and polymerase chain reaction. This report illustrates an asymptomatic Leishmania sp. infection that may have started on or from the canine venereal tumor tissue, the latter option further supporting previous evidence of such an alternative vector-independent route of transmission for canine visceral leishmaniasis in areas where these diseases coexist.